The Relevance of Mashlahat Theory for the Development of Contemporary Islamic Law: Study of Prevention COVID-19 in Indonesia - Hamzani, Achmad Irwan; Soeharto, Achmad; Aravik, Havis (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Mashlahat theory has historically been widely used in developing Islamic law. The public interest is a fundamental issue that must be considered when exploring Islamic law. The main objective of the development of Islamic law is to realize the mashlahat. This study examines the relevance of the mashlahat theory in the development of Islamic law. This research is a type of library research and uses a philosophical approach. Data were analyzed through content analysis. The results of this study indicate that the purpose of Islamic law is to realize and maintain the mashlahat. A mulism will get mashlahat if he can keep the five main aspects in the dharury group: religion, soul, intellect, lineage and honor, and property. On the other hand, we will get mafsadat if we cannot maintain it. The theory of mashlahat is very much needed to form Islamic law and respond to the times. Consideration of mashlahat is limited to issues other than ritual worship. Mashlahat theory has been applied since the beginning of the growth and development of Islam during the Khulafa al-Rasyidun period. Until now, many products of Islamic law have been produced by adhering to the principle of mashlahat. With the theory of mashlahat, Islamic law will not stagnate. All new problems can be solved from the perspective of Islamic law. With the consideration that mashlahat, too, can be realized, including in the context of the MUI fatwa in preventing the spread of Covid-19.